2018
DOI: 10.1007/s10439-018-2039-1
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality to Improve Walking Abilities in Cerebral Palsy: A Pilot Study

Abstract: Immersive virtual reality (IVR) offers new possibilities to perform treatments in an ecological and interactive environment with multimodal online feedbacks. Sixteen school-aged children (mean age 11 ± 2.4 years) with Bilateral CP-diplegia, attending mainstream schools were recruited for a pilot study in a pre-post treatment experimental design. The intervention was focused on walking competences and endurance and performed by the Gait Real-time Analysis Interactive Lab (GRAIL), an innovative treadmill platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
1
46
0
2
Order By: Relevance
“…In terms of movement kinematics, we presume that the explicit multisensory (i.e., visual–auditory–proprioceptive) feedback concerning the movement execution within the virtual environment could have allowed the patients to specifically time and control their movement patterns [see guidance hypothesis (61, 62)], thereby promoting a smooth movement pattern with reduced musculoskeletal co-contraction (18). In this review, several studies reported enhancement in gait kinematic scores (45, 50, 63, 64), which usually are adversely affected in children with cerebral palsy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In terms of movement kinematics, we presume that the explicit multisensory (i.e., visual–auditory–proprioceptive) feedback concerning the movement execution within the virtual environment could have allowed the patients to specifically time and control their movement patterns [see guidance hypothesis (61, 62)], thereby promoting a smooth movement pattern with reduced musculoskeletal co-contraction (18). In this review, several studies reported enhancement in gait kinematic scores (45, 50, 63, 64), which usually are adversely affected in children with cerebral palsy.…”
Section: Discussionmentioning
confidence: 97%
“…5.7 ± 1.4 out of 10, indicating, on average, a “good” quality of the studies. Here, one study scored 9 (40), one study scored 8 (41), three scored 7 (39, 42, 43), two scored 6 (44, 45), six scored 5 (37, 4650), and three studies scored 4 (38, 51, 52). The risk of biasing across the studies has been illustrated in Figure 2.…”
Section: Methods Summarymentioning
confidence: 99%
“…Ini dikarenakan keraguan terapis terhadap desain dan penggunaan kacamata realitas virtual yang kurang aman dan belum bisa memenuhi standar untuk digunakan pada CP. Dibalik kekhawatiran itu, telah banyak penelitian yang menunjukkan bahwa penggunaan realitas virtual dapat menjanjikan teknologi rehabilitasi yang lebih baik [6], [7], [8], [9], dan [10].…”
Section: Pendahuluanunclassified
“…This paradigm led to stronger sensory recalibration (32) and recruited different adaptation mechanisms (33) than non-immersive sensory alterations. Thanks to the recent development of lightweight HMDs, the use of VR has expanded to numerous applications designed for children, including neurodevelopmental research (30,(34)(35)(36), neurorehabilitation (37)(38)(39)(40), or distraction from painful medical procedures (41,42). Yet, the majority of these applications offer none or limited interactions with the virtual environment.…”
Section: Introductionmentioning
confidence: 99%